Tailored surgical management of a giant calculus in urethral diverticulum following post-hypospadias repair - Saini, Abhishek; Goel, Hemant Kumar; Sharma, Umesh; Yadav, Anoop; Singh, Dhirendra (Indian Journal of Case Reports, 2025)
Giant urethral calculi are rare, particularly within diverticula arising as late complications of hypospadias repair. We report a 30-year-old male with prior childhood hypospadias surgery who presented with a 2-year history of dysuria and lower urinary tract symptoms. Examination revealed a hard mass along the penile urethra, and imaging confirmed a 6×2 cm calculus within an anterior urethral diverticulum. After managing an associated urinary tract infection, the patient underwent Stage I Johansson’s urethroplasty with longitudinal incision, stone extraction, and diverticulectomy. Recovery was uneventful, with Stage II urethroplasty planned. This case highlights the importance of a tailored surgical approach addressing stone burden and anatomical anomalies, which is crucial for successful long-term outcomes.